A facile route to coat iron oxide nanoparticles with few-layer graphene - Mendes, Rafael Gregorio; Klingeler, Rüdiger (The journal of physical chemistry. C, Energy, materials, and catalysis, 2012)
The use of few-layer graphene coatings over nanoparticles is attractive, as it offers both long-term stability to the nanoparticles and renders them biocompatible due to the inert nature of the coating material. Moreover, graphitic coatings provide an easy platform for additional functionalization, making graphitic coated nanoparticles attractive candidates for multimodal therapeutics. Alternative strategies to coat nanoparticles often result in inhomogeneous coatings and unwanted contaminants that are hard to remove. In this work, we show the feasibility to use oleic acid as a precursor for the formation of multilayer graphene over iron oxide nanoparticles using a facile and clean route. The demonstrated graphitization process was driven by electron beam irradiation or thermal annealing. Thermal annealing leads to reduction of the iron oxide to pure iron and provides a means to tailor the magnetic properties of the multilayer graphene coated nanoparticles which are attractive as units for hyperthermia therapeutics. The graphitization process is also demonstrated over Si/SiO2 wafers.